Bone Marrow Concentrate Improves Early Cartilage Phase Maturation of a Scaffold Plug in the Knee: A Comparative Magnetic Resonance Imaging Analysis to Platelet-Rich Plasma and Control. (January 2016) - Krych, Aaron J.; Nawabi, Danyal H.; Farshad-Amacker, Nadja A.; Jones, Kristofer J.; Maak, Travis G.; Potter, Hollis G.; Williams, Riley J.
Background: Limited information exists on the clinical use of a synthetic osteochondral scaffold plug for cartilage restoration in the knee. Purpose/Hypothesis: The purpose of this study was to compare the early magnetic resonance imaging (MRI) appearance, including quantitative T2 values, between cartilage defects treated with a scaffold versus a scaffold with platelet-rich plasma (PRP) or bone marrow aspirate concentrate (BMAC). The hypothesis was that the addition of PRP or BMAC would result in an improved cartilage appearance. Study Design: Cohort study; Level of evidence, 3. Methods: Forty-six patients with full-thickness cartilage defects of the femur were surgically treated with a control scaffold (n = 11), scaffold with PRP (n = 23), or scaffold with BMAC (n = 12) and were followed prospectively. Patients underwent MRI with a qualitative assessment and quantitative T2 mapping at 12 months after surgery. An image assessment was performed retrospectively by a blinded musculoskeletal radiologist. The cartilage phase was measured by cartilage fill and quantitative T2 values on MRI. A comparison between groups after cartilage repair was performed. Results: The control scaffold group consisted of 8 male and 3 female patients (mean age, 38 years; mean body mass index [BMI], 25 kg/m 2 ), the PRP group had 15 male and 8 female patients (mean age, 39 years; mean BMI, 26 kg/m 2 ), and the BMAC group consisted of 8 male and 4 female patients (mean age, 36 years; mean BMI, 26 kg/m 2 ). The PRP-treated ( P = .002) and BMAC-treated ( P = .03) scaffolds had superior cartilage fill compared with the control group. With quantitative methods, the PRP group demonstrated a mean T2 value (49.1 ms) that was similar to that of the control scaffold group (42.7 ms; P = .07), but the BMAC group demonstrated a mean T2 value (60.5 ms) closer to that of superficial hyaline cartilage ( P = .01). The stratification of T2 values between the deep and superficial zones was not observed in any of the groups. Conclusion: In this comparative study, patients treated with scaffold implantation augmented with BMAC had improved cartilage maturation with greater fill and mean T2 values closer to that of superficial native hyaline cartilage at 12 months. Further work will determine if this translates into improved clinical outcomes.